EFFECTS OF MOTOR VEHICLES AND MOTOR VEHICLES ON THE ENVIRONMENT - Usmanov Ilhomjon Ikromjanovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides important information on the negative impact of car exhaust fumes on the environment and its consequences, as well as the prevention of greenhouse gas emissions.